Contagious fear: Escape behavior increases with flock size in European gregarious birds. Issue 10 (26th April 2019) - Morelli, Federico; Benedetti, Yanina; Díaz, Mario; Grim, Tomas; Ibáñez‐Álamo, Juan Diego; Jokimäki, Jukka; Kaisanlahti‐Jokimäki, Marja‐Liisa; Tätte, Kunter; Markó, Gábor; Jiang, Yiting; Tryjanowski, Piotr; Møller, Anders Pape
Abstract: Flight initiation distance (FID), the distance at which individuals take flight when approached by a potential (human) predator, is a tool for understanding predator–prey interactions. Among the factors affecting FID, tests of effects of group size (i.e., number of potential prey) on FID have yielded contrasting results. Group size or flock size could either affect FID negatively (i.e., the dilution effect caused by the presence of many individuals) or positively (i.e., increased vigilance due to more eyes scanning for predators). These effects may be associated with gregarious species, because such species should be better adapted to exploiting information from other individuals in the group than nongregarious species. Sociality may explain why earlier findings on group size versus FID have yielded different conclusions. Here, we analyzed how flock size affected bird FID in eight European countries. A phylogenetic generalized least square regression model was used to investigate changes in escape behavior of bird species in relation to number of individuals in the flock, starting distance, diet, latitude, and type of habitat. Flock size of different bird species influenced how species responded to perceived threats. We found that gregarious birds reacted to a potential predator earlier (longer FID) when aggregated in large flocks. These results support a higher vigilance arising from many eyes scanning in birds, suggesting that sociality may be a key factor in the evolution of antipredator behavior both in urban and rural areas. Finally, future studies comparing FID must pay explicit attention to the number of individuals in flocks of gregarious species. Abstract : Flight initiation distance (FID) is considered a proxy of antipredator behavior. We investigated intraspecific patterns of FID in relation to flock size in gregarious birds. A strong positive relationship between FID and flock size was found.